2000
DOI: 10.1007/pl00007881
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of intraocular lens power calculation after cataract surgery in patients with relative anterior microphthalmus

Abstract: In spite of the special anatomical conditions in patients with RAM the biometric formulas as modified by Haigis produced reliable IOL power calculations. The best accuracy was achieved when aiming at a target refraction in the range of +/-2 dptr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…18 There are few reports of cataract surgery in eyes with microcornea, and there are no studies of the use of transscleral-fixated PC IOLs in eyes with zonular dialysis. 5,6,[19][20][21][22][23][24][25][26][27][28] Gimbel et al 19 reported inserting PC IOLs in bilateral microcorneas with corneal diameters of 9.43 mm and 9.61 mm and ALs of 19.29 mm and 19.23 mm to obtain a postoperative bilateral CDVA of 20/20. Dahan 20 reported that with unilateral congenital and developmental cataracts, a pediatric PC IOL can be inserted in the capsular bag unless the corneal diameter is less than 9.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 There are few reports of cataract surgery in eyes with microcornea, and there are no studies of the use of transscleral-fixated PC IOLs in eyes with zonular dialysis. 5,6,[19][20][21][22][23][24][25][26][27][28] Gimbel et al 19 reported inserting PC IOLs in bilateral microcorneas with corneal diameters of 9.43 mm and 9.61 mm and ALs of 19.29 mm and 19.23 mm to obtain a postoperative bilateral CDVA of 20/20. Dahan 20 reported that with unilateral congenital and developmental cataracts, a pediatric PC IOL can be inserted in the capsular bag unless the corneal diameter is less than 9.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Inatomi et al 27 reported the most accurately predicted refraction using the SRK/T formula for microphthalmos and ALs of less than 19.0 mm. Bartke et al 28 used modified biometric formulas for cataract with microphthalmos in adulthood. Accurate IOL power calculation in complicated eyes with microcornea has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Inatomi et al15 reported the best predicted refraction was calculated using the SRK/T formula for microphthalmos with axial lengths less than 19.0 mm. Bartke et al27 used a modified biometric formulas for cataract with microphthalmos in adulthood. They showed 94.7% had not more than 3 diopters of difference between the target and achieved refraction and produced reliable IOL power calculations.…”
Section: Discussionmentioning
confidence: 99%
“…bei normal sein, die Refraktionswerte können auch den myopischen Bereich umfassen. Hierdurch setzt sich der relative anteriore Mikrophthalmus ( = RAM) vom sogenannten ¹Nanophthalmusª ab, der durch Bulbuslängen unter 20 mm definiert ist [1,2,4,5,6,7,8,9,11,12,13,16,17,21,22,23,24,25,26,27,28,29]. Tab.…”
unclassified
“…Wir haben in mehreren Studien, die sich mit dieser Patientengruppe beschäftigen [3,4,5,6,7,8,9], die anatomischen Besonderheiten herausgearbeitet und deren Auswirkungen auf operative Eingriffe (Kataraktoperation) und die Therapie der Glaukome in dieser Gruppe ausführlich untersucht. Der folgende Beitrag gibt einen Überblick über diese Studien.…”
unclassified